2015
DOI: 10.1007/s12603-015-0551-7
|View full text |Cite
|
Sign up to set email alerts
|

The associations of C-reactive protein with serum levels of polyunsaturated fatty acids and trans fatty acids among middle-aged men from three populations

Abstract: With the exception of consistent inverse association of CRP with total n-6 FAs, there are considerable variations across the three populations in the associations of CRP with different FAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…Studies have reported that n-3 FAs work both directly by substituting arachidonic acid as an eicosanoid substrate and stopping arachidonic acid metabolism, and indirectly by changing the expression of inflammatory genes via influences on transcription factor activation. [ 6 , 32 ] Additionally, it has been suggested that both n-3 PUFAs and n-6 PUFAs halt the activities of δ-6 desaturase, δ-5 desaturase, and cyclooxygenase, all of which have a role in fatty acid control that affects pro- and anti-inflammatory mediators. Therefore, high intake of both n-3 PUFAs and n-6 PUFAs could lessen inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that n-3 FAs work both directly by substituting arachidonic acid as an eicosanoid substrate and stopping arachidonic acid metabolism, and indirectly by changing the expression of inflammatory genes via influences on transcription factor activation. [ 6 , 32 ] Additionally, it has been suggested that both n-3 PUFAs and n-6 PUFAs halt the activities of δ-6 desaturase, δ-5 desaturase, and cyclooxygenase, all of which have a role in fatty acid control that affects pro- and anti-inflammatory mediators. Therefore, high intake of both n-3 PUFAs and n-6 PUFAs could lessen inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 , 5 ] The relationship between hs-CRP and dietary n-6 fatty acids (n-6 FAs) remains controversial. [ 6 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, apresentam implicação na gênese da obesidade e resistência à insulina (Saravanan et al, 2005), por suas ações deletérias, tanto nos parâmetros inflamatórios sistêmicos, como teciduais (fígado) (Longhi et al, 2016;El-Saed et al, 2016). Diante de sua relação com o aumento do risco cardiometabólico, estão sendo gradativamente substituídos pelas gorduras interesterificadas na indústria alimentícia.…”
Section: áCidos Graxos Alimentaresunclassified